Territorial Governance and Environmental Protection Volume 1: Urban Sprawl and Sustainable Urbanization - Keleş, Ruşen (2022)
As Cappadocia University, we are very much honored to publish this important contribution to the literature. The author, Professor Ruşen Keleş is the leading academician and intellectual of our country who raised generations of public administrators. This volume collected his articles written in English and is the only major source through which English-speaking readers can reach this rich collection. This field of urban, environment and local government has been a major topic throughout the last 200 years of Turkish modernization efforts. As the urbanization rapidly continues it will stay as important as it was in the past. The book will serve as a rich resource for academics and students working in these academic fields, as it contains theoretical and practical reviews on many main topics.